MySQL cookbook - Dubois, Paul (O'Reilly Media, 2014)
MySQL's popularity has brought a flood of questions about how to solve specific problems, and that's where this cookbook is essential. When you need quick solutions or techniques, this handy resource provides scores of short, focused pieces of code, hundreds of worked-out examples, and clear, concise explanations. Ideal for beginners and professional database and web developers, this updated third edition covers powerful features in MySQL 5.6 (and some in 5.7).
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed August 11, 2014)
Keywords: MySQL (Electronic resource); SQL (Computer program language); Database management; Relational databases; SQL (Langage de programmation); Bases de données; Gestion; Bases de données relationnelles